Bilateral Pathways from the Basal Forebrain to Sensory Cortices May Contribute to Synchronous Sensory Processing - Irene Chaves-Coira; Margarita L. Rodrigo-Angulo; Angel Nuñez (Frontiers in Neuroanatomy, 2018)
Sensory processing in the cortex should integrate inputs arriving from receptive fields located on both sides of the body. This role could be played by the corpus callosum through precise projections between both hemispheres. However, different studies suggest that cholinergic projections from the basal forebrain (BF) could also contribute to the synchronization and integration of cortical activities. Using tracer injections and optogenetic techniques in transgenic mice, we investigated whether the BF cells project bilaterally to sensory cortical areas, and have provided anatomical evidence to support a modulatory role for the cholinergic projections in sensory integration. Application of the retrograde tracer Fluor-Gold or Fast Blue in both hemispheres of the primary somatosensory (S1), auditory or visual cortical areas showed labeled neurons in the ipsi- and contralateral areas of the diagonal band of Broca and substantia innominata. The nucleus basalis magnocellularis only showed ipsilateral projections to the cortex. Optogenetic stimulation of the horizontal limb of the diagonal band of Broca facilitated whisker responses in the S1 cortex of both hemispheres through activation of muscarinic cholinergic receptors and this effect was diminished by atropine injection. In conclusion, our findings have revealed that specific areas of the BF project bilaterally to sensory cortices and may contribute to the coordination of neuronal activity on both hemispheres.